Food and Beverage Business Prospects during Covid-19 Pandemic - Azahari, Helmi; Fantini, Endah; Samsudin, Samsudin; Hermawan, Rudianto; Susanto, Imam (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aimed to determine the prospects for the food and beverages business during the Covid-19 pandemic, through observation of the food and beverages business marketing communication strategy, in this case, the restaurant. The Covid-19 pandemic has devastated the restaurant business. The loss of restaurant entrepreneurs in 2020 is estimated at more than IDR 1 trillion. The research was conducted using marketing communication theory, including publications and advertising for company promotion. Several previous studies have highlighted the impact of the Covid-19 pandemic on the restaurant business in Indonesia. Among them are Niko Al-Hakim (2021) and Liliyana (2020). However, this research is different because the object of observation is a restaurant business that was only opened during the Covid-19 pandemic. The research was conducted using descriptive qualitative methods with a case study approach. As a result, the use of marketing communication promotion tools, in the form of publications and advertisements with a specific target audience, is very effective for company promotion during a pandemic because it can convey marketing messages with a budget that is not too expensive.